Determinants of Exchange Rates in Somalia - Ibrahim, Mohamed Isse; Nageye, Ahmed Ibrahim (Asian Journal of Economic Modelling, 2017)
The purpose of this paper is to investigate the factors that determine exchange rates in Somalia and how those factors influence the exchange rates. To examine the relationship, a Monetary Approach to Exchange rate is employed to estimate the effects of trade balance, money supply, external debt and lack of government on exchange rate in Somalia for the period from 1970 to 2014 using MRA under OLS method. Main findings indicate that trade balance, money supply and external debt has a negative significant relationship to exchange rate in Somalia while lack of Government has a positive relationship to exchange rate. Also, this study examined some variables. Exchange rates also may be affected by some other factors that have not been considered in this study, so that this study recommends that central bank of Somalia should enact policies that improve the political factors it contributes towards gaining value of the Somalia shilling. This study adds lack of government to Monetary Approach Model, which has not been found in the scholarly literature.